2021
DOI: 10.1111/1365-2435.13968
|View full text |Cite
|
Sign up to set email alerts
|

The stabilising impact of natural selection on the allometry of sexual ornaments: Fish that escape locomotor constraints exhibit extravagant ornamentation

Abstract: 1. Positive allometry has been considered a hallmark of sexual selection whereby larger males of superior condition develop disproportionately larger ornaments for their body size compared to smaller males of poorer condition.2. Yet many structures known to be sexually selected often exhibit other allometric patterns. This has led to controversy over the utility of allometry in adequately capturing the signature of sexual selection, particularly if static (within population) and evolutionary (across species) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…Bolstad Egset et al, 2011Egset et al, , 2012Pelabon et al, 2013;Tobler & Nijhout, 2010; see also Dreyer et al, 2016;Knell et al, 2004;Lemaitre et al, 2014;Pelabon et al, 2014;Tidiere et al, 2017) or biomechanical (e.g. Barbosa & Moller, 1999;Basolo & Alcaraz, 2003;Summers & Ord, 2022;Swallow et al, 2000) constraints resulting from the expression of a large morphological structure. This 'plateauing' of the allometric relationship resulting in hypo-allometry in taxa with large (on average) dewlap sizes implies that it is not just the influence of habitat light and receiver distance operating on dewlap size, but additional perceptual, developmental or biomechanical constraints impacting changes in gross dewlap size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bolstad Egset et al, 2011Egset et al, , 2012Pelabon et al, 2013;Tobler & Nijhout, 2010; see also Dreyer et al, 2016;Knell et al, 2004;Lemaitre et al, 2014;Pelabon et al, 2014;Tidiere et al, 2017) or biomechanical (e.g. Barbosa & Moller, 1999;Basolo & Alcaraz, 2003;Summers & Ord, 2022;Swallow et al, 2000) constraints resulting from the expression of a large morphological structure. This 'plateauing' of the allometric relationship resulting in hypo-allometry in taxa with large (on average) dewlap sizes implies that it is not just the influence of habitat light and receiver distance operating on dewlap size, but additional perceptual, developmental or biomechanical constraints impacting changes in gross dewlap size.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, static allometries were computed across male lizards within each population (for those species with more than one studied population) and each species separately, for a total of 14 within‐taxon static allometries for Anolis and six within‐taxon static allometries for Draco . Our previous work on other animals has indicated that estimates of static allometry can be accurately computed when roughly 10 or more individuals have been sampled over a wide range of adult body sizes in a population (Summers & Ord, 2022 ). Furthermore, there was no association between the fit of computed static allometries and sample size (regression of R 2 as a function of N , Anolis : F 1,12 = 0.03, p = 0.86; Draco : F 1,4 = 0.06–0.13, p = 0.74–0.82; see also Tables S1–S3 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that allometric relationships result from strong constraints, which operate at different organizational levels independently from the taxonomic scale and which, on average, adhere to the predictions of MST. Yet, intraspecific variability in allometries are also frequently observed in animals (Kozłowski et al 2003a ; Sieg et al 2009 ; Summers and Ord 2021 ), and in plants (Vasseur et al 2012 ; Muir and Thomas-Huebner 2013 , 2015 ). For instance, the rate of respiratory metabolism has been found to scale isometrically ( i.e .…”
Section: Integrating Traits Across Scales: Biological Regularity Vers...mentioning
confidence: 98%
“…Bovidae: Bro-Jørgensen, 2007;Tidière et al, 2017;porcelain crabs, Petrolisthes: Baeza & Asorey, 2012). This may occur if sexual selection on weapon size is stronger in larger species and/or selection for larger weaponry creates a concomitant increase in body size (Summers & Ord, 2022).…”
mentioning
confidence: 99%